2012
DOI: 10.1038/ncomms1990
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion flow near room temperature in an ultralow current density

Abstract: The manipulation of spin textures with electric currents is an important challenge in the field of spintronics. many attempts have been made to electrically drive magnetic domain walls in ferromagnets, yet the necessary current density remains quite high (~10 7 A cm − 2 ). A recent neutron study combining Hall effect measurements has shown that an ultralow current density of J~10 2 A cm − 2 can trigger the rotational and translational motion of the skyrmion lattice in mnsi, a helimagnet, within a narrow temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
697
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 813 publications
(718 citation statements)
references
References 23 publications
8
697
1
3
Order By: Relevance
“…This value is an order of magnitude smaller than that for the HL as estimated in Fig. 2 and also as seen experimentally 19 . Fig.…”
Section: Discussionmentioning
confidence: 42%
“…This value is an order of magnitude smaller than that for the HL as estimated in Fig. 2 and also as seen experimentally 19 . Fig.…”
Section: Discussionmentioning
confidence: 42%
“…As an external magnetic field is increased, skyrmions emerge from a spiral state and their density initially increases and then decreases with field until the sample enters a uniform ferromagnetic state 2,3,9 . In bulk samples, skyrmions form three-dimensional (3D) line objects and occur in a limited range of fields and temperatures 2,16 , while for thin samples the skyrmions exhibit two-dimensional (2D) properties and are stable over a much larger range of fields and temperatures extending close to room temperature [4][5][6][7] . Skyrmions can be set into motion through the application of an external current 7,10,[18][19][20] , and it has been shown that there is a critical current above which the skyrmions depin into a sliding state [19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…In bulk samples, skyrmions form three-dimensional (3D) line objects and occur in a limited range of fields and temperatures 2,16 , while for thin samples the skyrmions exhibit two-dimensional (2D) properties and are stable over a much larger range of fields and temperatures extending close to room temperature [4][5][6][7] . Skyrmions can be set into motion through the application of an external current 7,10,[18][19][20] , and it has been shown that there is a critical current above which the skyrmions depin into a sliding state [19][20][21][22][23][24][25][26] . Skyrmion motion can be directly observed with Lorentz microscopy 7,10 or deduced from changes in the transport properties, permitting the construction of effective skyrmion velocity versus applied force curves that show that the skyrmion velocity increases with increasing current 20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations